Rapid Prototyping In Orthopeadics: Principles And Applications. - Abdullah, Jamaluddin; Hassan, Ahmad Yusoff (World Scientific Publishing, 2005)
Rapid prototyping (RP) is primarily concerned with automated fabrication of tangible model or prototype from computerised data or any computer aided design (CAD) system for visualisation, testing and verification.